Recent Trends in Discourse and Dialogue - Dybkjær, Laila (Springer, 2017)
This book is a collection of eleven chapters which together represent an original contribution to the field of (multimodal) spoken dialogue systems. The chapters include highly relevant topics, such as dialogue modeling in research systems versus industrial systems, evaluation, miscommunication and error handling, grounding, statistical and corpus-based approaches to discourse and dialogue modeling, data analysis, and corpus annotation and annotation tools. The book contains several detailed application studies, including, e.g., speech-controlled MP3 players in a car environment, negotiation training with a virtual human in a military context, application of spoken dialogue to question-answering systems, and cognitive aspects in tutoring systems. The chapters vary considerably with respect to the level of expertise required in advance to benefit from them. However, most chapters start with a state-of-the-art description from which all readers from the spoken dialogue community may benefit. Overview chapters and state-of-the-art descriptions may also be of interest to people from the human-computer interaction community.